2006
DOI: 10.1007/bf02850210
|View full text |Cite
|
Sign up to set email alerts
|

Determination of risk factors for hypertension through the classification tree method

Abstract: Most current statistical strategies for determining risk factors for hypertension (HT) among certain populations have proved inconclusive. In this study, the classification tree method, which is more practical and easy to understand than other statistical methods, was used to determine the risk for HT among outpatients in a clinic in Denizli province, western Turkey, between January 2002 and July 2004. The effects of 14 risk factors (body mass index, waist-to-hip ratio, age, serum total cholesterol, serum trig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 25 publications
1
4
0
Order By: Relevance
“…Among the 20 selected features in this study, BMI, SBP, TG level, Cr level, LDL-C level, and glucose level had a strong effect on hypertension prediction and were included among the top 10 in the ranking of the feature importance for all three models. Similar to the results of previous studies, features such as age ( 27 29 ), BMI ( 28 , 30 ), diabetes status ( 28 ), Cr level ( 26 ), blood pressure ( 29 ), WC ( 31 ), smoking status ( 28 ), LDL-C level ( 26 , 28 ), HDL-C level ( 26 ), drinking ( 28 ), glucose level ( 32 ), TC level ( 26 , 27 ), exercise ( 33 ), salt intake ( 34 ), and TG level ( 27 ) were identified as predictors of hypertension in the risk assessment model of hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…Among the 20 selected features in this study, BMI, SBP, TG level, Cr level, LDL-C level, and glucose level had a strong effect on hypertension prediction and were included among the top 10 in the ranking of the feature importance for all three models. Similar to the results of previous studies, features such as age ( 27 29 ), BMI ( 28 , 30 ), diabetes status ( 28 ), Cr level ( 26 ), blood pressure ( 29 ), WC ( 31 ), smoking status ( 28 ), LDL-C level ( 26 , 28 ), HDL-C level ( 26 ), drinking ( 28 ), glucose level ( 32 ), TC level ( 26 , 27 ), exercise ( 33 ), salt intake ( 34 ), and TG level ( 27 ) were identified as predictors of hypertension in the risk assessment model of hypertension.…”
Section: Discussionsupporting
confidence: 89%
“…For instance, in a study by Chang et al, a different mining tool was employed, revealing significant results that underscored the association of triglycerides, creatinine, age, and uric acid with hypertension risk [ 20 ]. Similarly, Akdag et al utilized decision trees to identify BMI, waist/hip ratio, gender, and triglycerides as notable risk factors for hypertension [ 21 ]. Another study conducted in Qatar by AlKaabi et al yielded comparable results using random forest and logistic regression analyses, emphasizing the importance of age, physical activity, fruit and vegetable consumption, and diabetes history as critical predictors of hypertension [ 5 ].…”
Section: Discussionmentioning
confidence: 99%
“…They found that old age, body mass index and low education attainment are significant risk factors. Akdag et al (2006) applied the classification tree method to determine risk factors for hypertension among 1761 adults at the outpatient clinic in western Turkey between January 2002 and July 2004. They studied the effects of fourteen risk factors on hypertension, and their results revealed that body mass index, waist-to-hip ratio, sex, serum triglycerides, serum total cholesterol, hypertension in first-degree relatives, and saturated fat consumption are main risk factors.…”
Section: Related Workmentioning
confidence: 99%